Application of artificial insemination on poultry in Ethiopia - Zelleke, G.; Ayalew, W. (Ethiopian Society of Animal Production, 2004)
This paper reviews the current status of application of artificial insemination (AI) in poultry in Ethiopia. The technique was not practiced in the country before 2002. The application of AI in chicken in Ethiopia has been tested by comparing natural mating (NM), natural mating plus artificial insemination (NM+AI) and AI alone with the semen from selected Rhode Island Red (RIR) cocks. Higher fertility and hatchability were recorded in NM+AI (93.33%) and 80.18%) groups as compared to NM (81.18% and 72.27%) or AI (83.86% and 78.85%) groups, respectively. Observations from this result provide satisfactory evidence that AI can be applied in poultry production sector. Further, AI can efficiently be exploited to maximize the utilization of cocks of high fertility and hatchability, thereby reducing the need for acquiring new batches of male breeding stock.